Design, Development, and Control of a Robotic Gripper for Activities of Daily Living (ADL) Assistance. - (:unkn) unknown (My University, 2022)
This research contributes to developing a robotic gripper designed to improve the performance of assistive robots to help people with upper limb impairment due to stroke, injury, and other trauma. As developed in this research, the gripper for assistive robots (GAR) can be an alternative solution to the existing robotic grippers increasing the benefits in different ways, including the cost/benefits ratio and the range of graspable objects. The GAR has been designed with simplicity in mind with a minimum viability approach. The design, construction, control, and operation of this robotic hand have been simplified with a minimal number of custom-made components, resulting in a remarkable performance. In addition, GAR's rigidity allows it to hold objects weighing up to 5 kilograms without deforming or compromising its internal mechanism.Various experiments mimicking real-world application scenarios have been performed to measure in quantitative and qualitative ways the performance of GAR to evaluate the proposed design.
Keywords: Assistive Robot; Design; Gripper; Robotic Hand